PENDAMPINGAN REDESAIN LOGO UMKM ANGGOTA HIMPUNAN WANITA DISABILITAS INDONESIA BALI SEBAGAI UPAYA MENUJU MASYARAKAT INKLUSIF - Ni Putu Tirka Widanti; Ayu Putu Utari Parthami Lestari; Luh Riniti Rahayu; I Made Kartika; Sri Sulandri (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
Women and people with disabilities are some of the minority groups that are excluded from development. Especially if both are experienced by one individual simultaneously. HWDI is a social organization that accommodates women with physical limitations. HWDI in Bali actively mobilizes its members to be empowered and independent. Ngurah Rai University through community service activities has been present in the midst of Bali HWDI members for 3 months since October 2022 and provided assistance to one of its members regarding redesigning a business logo. Logo redesignation was chosen as the community service activity because of its urgency. The previous logo was not representative enough to be used as promotional capital because it did not reflect the character of the business and the business owner, had weaknesses in design principles (choice of color), had low resolution, and still had a watermark. The method of implementing the activity was the type of action research with a mix-method. The approach was carried out by understanding the characteristics of partners to the type of business. Thus, through understanding design and logo theory, a business logo is created that is different from the initial logo. Logos that are designed with careful consideration produce an output with a special character. Efforts to explore the uniqueness of the product and the owner of the partner business produce a logo that fits the partner's promotional needs.